Biomass derived metal carbide catalysts formed using a salt flux synthesis. (9th October 2019) - Harris, Daniel; Budhi, Sridhar; She, Yuqi; Henry, Jonah; Leonard, Brian M
Abstract: Metal carbide compounds have recently become highly studied materials as non-precious metal catalysts for several energy related reactions. These materials often require high temperatures and long annealing time to produce the desired phase. Using a low-temperature salt flux synthesis method, molybdenum metal and biomass samples were reacted to form porous nanoparticle Mo2 C. Several different biomass and biochar sources were used to demonstrate the versatility and generality of this process. The biomass derived carbides were also tested and shown to be active for the Hydrogen Evolution Reaction (HER). In addition to abundant and inexpensive carbon sources, the overall reaction takes place at reduced temperatures compared to traditional carbide synthesis methods and utilizes very simple and environmentally friendly techniques. This process provides a clear path toward greener carbide synthesis using economical and renewable resources and could be implemented using nearly any biomass available.